Biological Control of Potato Common Scab With Rare Isatropolone C Compound Produced by Plant Growth Promoting Streptomyces A1RT - Sarwar, Arslan; Latif, Zakia; Zhang, Songya; Zhu, Jing; Zechel, David L.; Bechthold, Andreas (Frontiers in Microbiology, 2018)
Potato is prone to many drastic diseases like potato common scab (CS). As no highly effective methods exist for managing CS, this study explored the possibility of using biological control. Ten bacterial strains were isolated from CS-infected potato tubers from four different locations of Punjab, Pakistan, and identified based on biochemical and molecular analysis. Analysis of 16s rDNA sequences amplified by PCR revealed the isolated bacterial strains to be Streptomyces scabies, S. turgidiscabies and S. stelliscabies. Pathogenic islands were also confirmed among the isolates after identification of txtAB, nec1 and tomA genes with PCR amplification. One strain isolated from soil was antagonistic to the pathogenic Streptomyces spp., and determined to be Streptomyces A1RT on the basis of 16s rRNA sequencing. A methanolic extract of Streptomyces A1RT contained Isatropolone C, which was purified and structurally determined by 1H- and 13C-NMR, 1H/1H-COSY, HMQC, and HMBC techniques. Streptomyces A1RT also produced the plant growth hormone indole-3-acetic acid (IAA) with a titer of 26 µg ml-1 as confirmed by spectrophotometry and HPLC. In a greenhouse assay, disease severity index was established from 0 to 500. Average disease severity indexes were recorded as 63, 130.5 and 78 for Streptomyces scabies, S. turgidiscabies and S. stelliscabies, respectively. When Streptomyces A1RT was applied in soil that contained one of these pathogenic isolates, the average disease severity indexes were significantly (P < 0.05) reduced to 11.1, 5.6 and 8.4, respectively. A significant increase in tuber weight and shoot development was also observed with the tubers treated with Streptomyces A1RT. The use of the plant growth-promoting Streptomyces A1RT against potato CS thus provides an alternative strategy to control the disease without affecting environmental, plants, animals and human health.